2017
DOI: 10.1021/acsmacrolett.7b00649
|View full text |Cite
|
Sign up to set email alerts
|

Pulsating Polymer Micelles via ATP-Fueled Dissipative Self-Assembly

Abstract: Energy dissipation underlies dynamic behaviors of the life system. This principle of biology is explicit, but its in vitro mimic is very challenging. Here we use an energy-dissipative self-assembly pathway to create a life-like polymer micellar system that can do periodic and self-adaptive pulsating motion fueled by cell energy currency, adenosine triphosphate (ATP). Such a micelle expansion−contraction behavior relies on transient supramolecular interactions between the micelle and ATP fuel. The micelles capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…In the absence of reported kinetic parameters for all reaction steps in published examples of self-assembling systems relying on chemical fuel consumption, 11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] it is impossible to certify in an unambiguous manner whether these systems exploit a chemically-driven information ratchet mechanism. Such an analysis is further hampered by the fact that most examples rely on the batch-wise addition of fuel, in which high-energy species may indeed be transiently observed, but not necessarily because of asymmetric energy consumption.…”
Section: Perspective and Outlookmentioning
confidence: 99%
“…In the absence of reported kinetic parameters for all reaction steps in published examples of self-assembling systems relying on chemical fuel consumption, 11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] it is impossible to certify in an unambiguous manner whether these systems exploit a chemically-driven information ratchet mechanism. Such an analysis is further hampered by the fact that most examples rely on the batch-wise addition of fuel, in which high-energy species may indeed be transiently observed, but not necessarily because of asymmetric energy consumption.…”
Section: Perspective and Outlookmentioning
confidence: 99%
“…Synthetic chemical‐fuel driven self‐assembly processes have been reported that also rely on noncovalent interactions between the building blocks and a chemical fuel . However, while most cases allude to similarities with microtubule formation or related biological dissipative processes, it turns out that in all the cases reported so far, a fundamentally different mechanism is operative (Figure b) . Contrary to what happens in Nature, energy dissipation, intended as the release of energy stored in the chemical fuel, is not catalysed by the building blocks, but rather by external elements such as an enzyme.…”
Section: Figurementioning
confidence: 99%
“…Moreover, both the time when the material is released as well as the sequence of the released dyes can be predetermined by the users. These studies, as well as other from the field, show the exciting possibilities of dissipative supramolecular materials as drug delivery vehicles or other biomaterials in the future.…”
Section: Supramolecular Materials With a Tunable Lifetimementioning
confidence: 80%